STRATEGI DAKWAH COFFEE SHOP: STUDI KASUS SADAR COFFEE UNTUK MEMBERIKAN KEBERMANFAATAN TERHADAP KARYAWAN CAFE DAN MASYARAKAT RW 05 CIGANJUR - Abdullah Azzam Umair; Luqman (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
The purpose of this study is to determine how the missionary strategy of a coffee shop called Sadar Coffee can provide benefits for all cafe employees and the surrounding community, especially RW 05 Ciganjur, by using a SWOT analysis approach and formulating how to apply, implement and evaluate the missionary strategy. The formulation of the problem in this study is how to apply strategies, implementation and evaluation of the preaching carried out by the Sadar Coffee shop to provide benefits to cafe employees and the community of RW 05 Ciganjur. The conclusion of this study is that the strategy of the Sadar cafe da'wah used to provide benefits to cafe employees and the community of RW 05 Ciganjur by means of the Sadar Sharing and Class Sadar programs. At the stage of implementing the Sadar Coffee da'wah strategy, the SWOT analysis approach is used. And implemented with the Sadar Sharing and Class Sadar programs which are filled with da'wah activities such as sharing Friday blessings, orphanages and regular weekly religious studies. As for the evaluation stage, attention must be paid to the SWOT elements such as strengths, weaknesses, opportunities and threats so that they can be used as learning for the future.